Anduan Pembelajaran Klinik Keperawatan: Inisiasi Pengembangan Peran Perawat Pendidik - Rizky Indriasari (Indonesian Journal of Nursing Scientific, 2023)
Nurse educators play an important role in nursing clinical learning in hospitals. Nurse educators design high-quality learning for nurses and nursing students according to learning needs. This study aims to initiate the development of the role of nurse educators through nursing clinical learning guidelines. The method used was a case study with an action research approach. The findings showed that the clinical care manager's role as a nurse educator was able to understand nursing education and skills needs, design learning and apply research findings to improve nursing care. 80% of nurses felt comfortable with the learning culture, work environment conducive to learning and high motivation to learn. 84% of nurses were satisfied with the clinical learning methods provided by nurse educators such as nursing care rounds, case reports, journal reading, bed side teaching, one day one clinical question, preceptorship-mentorship-coaching which are conducted regularly at least once a month. However, currently there is no nursing clinical learning guide that can be a reference for nurse educators so that the role of nurse educators has not been optimally developed. Conclusion: Support from the nursing department, nursing committee and hospital management is needed to design nursing clinical learning guidelines to fully develop the role of nurse educators in nursing education in hospitals.